Results of the Pacific Branch of VNIRO (TINRO) activities in the information support of the 2021 salmon fishing season in Russian Far East - E. A. Shevlyakov; A. N. Kanzeparova; A. A. Somov; V. A. Shevlyakov; A. N. Starovoytov; R. L. Batanov; E. I. Barabanschikov (Известия ТИНРО, 2022)
The article analyzes the sea trawl surveys on pink salmon and their interrelation with the values of pink salmon returns to the main spawning water bodies of the Bering and Okhotsk Seas. According to the fall trawl surveys in the Bering and Okhotsk Seas, the number of juvenile pink salmon was 1.05 and 2.10 billion, respectively. These estimates supposed return of 200 mln pink salmon in 2021 in the Bering Sea (catch — 160–180 thousand tons, 50 mln — pass to spawning groungs), 200–270 mln in the Sea of Okhotsk (catch in the western Kamchatka — 200– 250 thousand tons, 50 mln — pass), Mainland coast of the Sea of Okhotsk — 20–30 thousand tons, 13 mln — pass, eastern Sakhalin and Kurils — 20–25 thousand tons, 5–10 mln — pass). Results of summer trawl surveys of prenadromous pink salmon showed high level winter survival and confirmed earlier returns estimations. The actual pink salmon catch in the Sea of Okhotsk and Bering Sea basins of the Far East was 424.000 tons, which was close to the overall average forecasted catch of 418.000 tons. The Pacific salmon catch in the TINRO area of responsibility (Primorsky Krai and Chukotka AD) was 5.711 thousand tons (5.496 thousand tons — Chukotka AD, 0.215 thousand tons — Primorsky Krai).